THE MEDIATION ROLE OF EXTRA ROLE: ORGANIZATIONAL SUPPORT AND INFORMATION TECHNOLOGY ON EMPLOYEE PERFORMANCE - Nurlasera Nurlasera; Uzoma Ononye; Qori Al Banin; Mayaastuti Mayaastuti; Yusmedi Nur Faizal (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
The purpose of this study is to test and analyze the mediation role of extra role behavior on the influence of organizational support and information technology on Micro Small and Medium Enterprises (MSME) actors. Method in this study is a quantitative study. Where questionnaires are used to collect data, there are 189 respondents in the form of MSME actors who focus on female gender. Data analisys in this study using tools in the form of SEM-PLS. The results obtained are that extra role behavior is able to be a mediating variable in the indirect influence test has a positive and significant impact, on the other hand for the direct influence test also has a positive and significant influence. It is clear that the independent variable is able to be a good predictor of success in employee performance in making an art in this case traditional food as one of the cultural characteristics of the Riau Islands. The novelty in this study is the success of the extra role behavior possessed by women in making products that are more valuable.